Volatile fraction from Lippia alba: evaluation of its antioxidant property and identification of compounds by GC-MS/GC-FID - Pereira, Rosângela Santos; Pereira, Rafael Santos; Aguiar, Rosane Moura; Lemos, Gisele da Silveira; Junior, Baraquizio Braga do Nascimento; Oliveira, Djalma Menezes de (Scientia Plena, 2019)
The volatile fraction from Lippia alba cultivated in the garden of medicinal plants of the Universidade Estadual do Sudoeste da Bahia, Brazil was obtained using the simultaneous distillation-extraction (SDE) process. This volatile fraction was analyzed by GC-MS/GC-FID and its antioxidant property was evaluated through DPPH* method using gallic acid as standard reference. The volatile fraction shown low property to scavenge the DPPH* free radicals, in comparison to gallic acid. Thirty-four constituents were identified, and the main monoterpene compounds were carvone (53.8%) and limonene (12.6%). Germacrene D (7.9%) was identified among the sesquiterpenes. The concentration of carvone and limonene were equivalent to 2/3 of the total content of the volatile fraction, which gives it industrial value, mainly as flavoring agent. The small concentration of myrcene and the absence of citral in the composition of the volatile fraction of L. alba from Jequié confirmed the classification of this species as belonging to chemotype III (carvone-limonene), a variety that occurs in the Northeastern of Brazil.